2015
DOI: 10.1002/2015gl064796
|View full text |Cite
|
Sign up to set email alerts
|

Injection of iodine to the stratosphere

Abstract: We report a new estimation of the injection of iodine into the stratosphere based on novel daytime (solar zenith angle < 45°) aircraft observations in the tropical tropopause layer and a global atmospheric model with the most recent knowledge about iodine photochemistry. The results indicate that significant levels of total reactive iodine (0.25–0.7 parts per trillion by volume), between 2 and 5 times larger than the accepted upper limits, can be injected into the stratosphere via tropical convective outflow. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
73
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(86 citation statements)
references
References 36 publications
12
73
1
Order By: Relevance
“…The tropospheric VCD of ∼ 2.3 ± 0.7 × 10 13 molec cm −2 BrO derived from this study falls in the range of other currently reported measurements, which span from ∼ 1 to 3 × 10 13 molec cm −2 Salawitch et al, 2005;Theys et al, 2007Theys et al, , 2011Coburn et al, 2011;Wang et al, 2015). The observed tropospheric BrO VCD is consistent with the VCD of 2.0 × 10 13 molec cm −2 measured by the same instrument during a previous study in the same location (Coburn et al, 2011).…”
Section: S Coburn Et Al: Mercury Oxidation From Bromine Chemistry Isupporting
confidence: 89%
See 1 more Smart Citation
“…The tropospheric VCD of ∼ 2.3 ± 0.7 × 10 13 molec cm −2 BrO derived from this study falls in the range of other currently reported measurements, which span from ∼ 1 to 3 × 10 13 molec cm −2 Salawitch et al, 2005;Theys et al, 2007Theys et al, , 2011Coburn et al, 2011;Wang et al, 2015). The observed tropospheric BrO VCD is consistent with the VCD of 2.0 × 10 13 molec cm −2 measured by the same instrument during a previous study in the same location (Coburn et al, 2011).…”
Section: S Coburn Et Al: Mercury Oxidation From Bromine Chemistry Isupporting
confidence: 89%
“…compared ground-based and balloon-borne measurements to VCDs of BrO from the space-borne Global Ozone Monitoring Experiment (GOME) and found all platforms were consistent with a rather widespread tropospheric BrO VCD of 1-3 × 10 13 molec cm −2 once appropriate radiative transfer effects were taken into consideration. Salawitch et al (2005) and Theys et al (2011) also report satellite derived tropospheric BrO VCDs (GOME and GOME-2, respectively) for the midlatitudes of 2 × 10 13 and 1-3 × 10 13 molec cm −2 , respectively. Ground-based measurements Coburn et al, 2011) in the midlatitudes have reported BrO VCDs of 1-2 × 10 13 molec cm −2 that are comparable to the findings from satellites.…”
Section: Introductionmentioning
confidence: 99%
“…Tropical annual averages have been computed between 20°N and 20°S, while the tropical Western Pacific (TWP) warm pool area in February has been used as a representative region with strong vertical convection (0° ≤ latitude ≤ 20°N; 120°E ≤ longitude ≤ 165°E). In the absence of measurements of atomic bromine or iodine in the free and upper troposphere, our CAM‐Chem halogen configuration has been validated with observed vertical profiles of the commonly targeted BrO [ Dorf et al , ] and IO [ Saiz‐Lopez et al , ] radicals in the tropical atmosphere (see supporting information).…”
Section: Resultsmentioning
confidence: 99%
“…If iodic acid is irreversibly lost on aerosol (similar to sulfuric acid) its lifetime should only be on the order of several minutes at typical boundary layer conditions. Therefore, the presence of iodine indicates either a local iodine source or its transport from marine environments in the form of a reservoir substance, e.g., CH 3 I (the lifetime of CH 3 I is in the order of 1 week; see Saiz-Lopez et al, 2015), and subsequent release due to photolysis.…”
Section: Iodic Acid (Hio 3 ) and Oiomentioning
confidence: 99%